Probing the Debye Dielectric Relaxation in Supercooled Methanol - Li, Xin; Chen, Zeming; Gao, Yanqin; Tu, Wenkang; Wang, Li-Min (Frontiers in Materials, 2015)
The explanation of the dielectric dynamics in methanol would offer knowledge of the Debye relaxation in supercooled monoalcohols. However, due to the fast crystallization, it is hard to attain the dynamics of pure methanol in the deeply supercooled region. In this paper we studied the dynamics of methanol - 2-ethyl-1-hexanol mixtures with methanol concentration up to 80 mol% using dielectric and calorimetric measurements. Two main relaxations are detected in the dielectric spectra of the mixtures, and the slower one generally reproduces the Debye relaxation features reported in earlier studies of other monoalcohols. The validity of the ideal mixing law is verified for the relaxation time of the slower dynamics in the mixtures. The results suggest that the Debye relaxation is present in the dielectric spectra of methanol. The temperature dependence of the Debye relaxation time is constructed for the supercooled methanol.